Flowers as Ornaments in Room Accessories Based on Ribbon and Macramé Techniques - Putri, Martaleny Kurnia Zazilah; Jupriani, Jupriani (Institut Seni Indonesia Padang Panjang, 2025)
The aim of this final work is to create and introduce creative ideas for craft arts using ribbon and macrame techniques as the completion of the final work. Then introduce to the general public what ribbon flowers and macrame are, then later they will be educated as a display idea in the area of the room which has a function as decoration on thatch media. The method that the author uses is a method that has been proposed in creating art which is carried out in stages, namely the preparation stage by searching for information, elaboration by analyzing the problem, synthesis expressing ideas, realization of the concept by creating the work and completion by doing it together. Based on the method that has been carried out to produce seven various flower works as ideas for creating works with ribbons and macrame the author creates works in the form of accessories. The rooms have the titles: Matahri 1, Mataharri 2, Matahari 3, Matahari 4, Seluran 1, Seluran 2, Tangga